2014
DOI: 10.9721/kjfst.2014.46.4.505
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-inflammatory Activities of Water-soluble Extracts from Different Parts of Kojongsi Persimmon (Diospyros kaki L.)

Abstract: Kojongsi persimmon (Diospyros kaki L.) is the major cultivar of dried persimmon in Korea. The purpose of this study was to investigate the antioxidant and anti-inflammatory activities of water-soluble extracts from the calyx (PCE), peel (PPE) and leaf (PLE) of Kojongsi persimmon. PCE showed the highest total phenolic and flavonoid contents. In addition, the antioxidant activities (diphenylpicrylhydrazyl, 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid), nitric oxide and reducing power) of PCE were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Likewise, flavonoids and terpenoids were identified from the Korean PL and it was found that kaempferol and quercetin derivatives, mainly those with galloyl moieties, exhibited strong antioxidant activities using DPPH and HPLC-ABTS assays [ 16 ]. Furthermore, water-soluble PL extracts showed strong antioxidant activities using DPPH, ABTS, nitric oxide (NO), and reducing power assays [ 68 ], whereas methanolic extracts were able to decrease the production of malondialdehyde (MDA) [ 84 ]. Similarly, Li et al [ 75 ] stated that flavonoids of PL decreased MDA production and increased superoxide dismutase (SOD) activity in hyperlipidemic rats.…”
Section: Pharmacological Effects Of Plmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, flavonoids and terpenoids were identified from the Korean PL and it was found that kaempferol and quercetin derivatives, mainly those with galloyl moieties, exhibited strong antioxidant activities using DPPH and HPLC-ABTS assays [ 16 ]. Furthermore, water-soluble PL extracts showed strong antioxidant activities using DPPH, ABTS, nitric oxide (NO), and reducing power assays [ 68 ], whereas methanolic extracts were able to decrease the production of malondialdehyde (MDA) [ 84 ]. Similarly, Li et al [ 75 ] stated that flavonoids of PL decreased MDA production and increased superoxide dismutase (SOD) activity in hyperlipidemic rats.…”
Section: Pharmacological Effects Of Plmentioning
confidence: 99%
“…Furthermore, they also inhibited prostaglandin E2 (PGE2) and NO production in LPS-activated RAW 264.7 cells, suppressed interleukin-6 (IL-6), TNF-α, and IL-1β levels, and decreased protein expression of iNOS and cyclooxygenase-2. Similarly, water-soluble extracts obtained from PL were a rich source of phenolic compounds, which suppressed the production of inflammatory mediators (NO and PGE2) and pro-inflammatory cytokines (TNF-α and IL-1β) in LPS-stimulated RAW 264.7 macrophages [ 68 ].…”
Section: Pharmacological Effects Of Plmentioning
confidence: 99%
“…Persimmons are generally classified into two groups: sweet (non-astringent) and astringent persimmons, depending on the degree of astringency. Most native cultivars in Korea, such as Kojongsi, Chengdo-Bansi, Dungsi, Sagoksi, Danseongsi, Weolhasi and so on, are astringent persimmons (Jeon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The cultivation status of Kojongsi persimmon is 11.5% among all persimmon varieties, but it is known as a special local crop, because most Kojongsi persimmon trees grow in the Gyeongsangnam-do area in Korea (Jeon et al, 2014). Because of its astringent taste, Kojongsi persimmon is processed by drying only the pulp without the peel (gotgam) (Chung et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation